2014
DOI: 10.1093/mp/ssu070
|View full text |Cite
|
Sign up to set email alerts
|

Spatial H2O2 Signaling Specificity: H2O2 from Chloroplasts and Peroxisomes Modulates the Plant Transcriptome Differentially

Abstract: Hydrogen peroxide (H2O2) operates as a signaling molecule in eukaryotes, but the specificity of its signaling capacities remains largely unrevealed. Here, we analyzed whether a moderate production of H2O2 from two different plant cellular compartments has divergent effects on the plant transcriptome. Arabidopsis thaliana overexpressing glycolate oxidase in the chloroplast (Fahnenstich et al., 2008; Balazadeh et al., 2012) and plants deficient in peroxisomal catalase (Queval et al., 2007; Inzé et al., 2012) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
157
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 93 publications
4
157
1
1
Order By: Relevance
“…7A). Thus, our RNA-seq and RT-qPCR transcriptomic analyses further strengthen the connection between distinct biotic and abiotic stresses and changes in sterol composition, in particular those affecting the stigmasterol-to-b-sitosterol ratio (Grunwald, 1978;Whitaker, 1994;Griebel and Zeier, 2010;Wang et al, 2012b;Senthil-Kumar et al, 2013;Sewelam et al, 2014), which declines sharply upon the silencing of FPS (Fig. 3B).…”
Section: Plants Perceive a Reduction Of Major Sterols As A Stress Signalsupporting
confidence: 63%
“…7A). Thus, our RNA-seq and RT-qPCR transcriptomic analyses further strengthen the connection between distinct biotic and abiotic stresses and changes in sterol composition, in particular those affecting the stigmasterol-to-b-sitosterol ratio (Grunwald, 1978;Whitaker, 1994;Griebel and Zeier, 2010;Wang et al, 2012b;Senthil-Kumar et al, 2013;Sewelam et al, 2014), which declines sharply upon the silencing of FPS (Fig. 3B).…”
Section: Plants Perceive a Reduction Of Major Sterols As A Stress Signalsupporting
confidence: 63%
“…3). In accordance with these findings, it was reported that drought stress led to a decrease in the Fv/Fm ratio in bean plant, STUDY OF THE INTERACTIVE EFFECTS OF CALCIUM ... suggesting chronic photo-inhibition due to photooxidation of photosynthetic apparatus (Sewelam et al, 2014) and damage to the PSII oxygenevolving complex possibly attributable to D1 protein damage under drought stress (Zlatve & Yordanov, 2004). Likewise, it was suggested that the photosynthetic efficiency has been declined in Nothofagus species under drought stress (Piper et al, 2007 andLuo et al, 2015).…”
Section: Calcium and Aba Alleviate The Inhibiting Effects Of Drought mentioning
confidence: 56%
“…The data indicate that ROS and redox signaling participate in early retrograde signaling (Gläßer et al, 2014). Conditional H 2 O 2 generation in chloroplasts or peroxisomes elicits distinct changes in gene expression (Sewelam et al, 2014). Chloroplast H 2 O 2 causes the up-regulation of transcripts involved in early signaling (including transcription factors), secondary signaling, mitochondrial retrograde signaling, and the biosynthesis of defense compounds in a time-dependent manner (Sewelam et al, 2014).…”
Section: Transmission Of Redox and Ros Signals To The Cytosolmentioning
confidence: 99%